2009
DOI: 10.1080/00015458.2009.11680384
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Cystic Artery Rupture: a Rare Cause of Haemoperitoneum

Abstract: We report the case of a 74-year-old man who presented an acute haemoperitoneum further to the rupture of the cystic artery. The bleeding was successfully controlled using embolization. This procedure was complicated by ischaemic necrosis and perforation of the gall-bladder requiring laparoscopic cholecystectomy. Spontaneous rupture of intra-abdominal arteries is a rare event. This usually occurs in abnormal arteries, presenting pseudo-aneurysm or, weakened by arterial hypertension, diabetes or corticotherapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…15 28 In these cases, surgical intervention was avoided either due to a presumed high risk of mortality or patient refusal.…”
Section: Discussionmentioning
confidence: 99%
“…15 28 In these cases, surgical intervention was avoided either due to a presumed high risk of mortality or patient refusal.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier review 13 such cases were identified [14] thereafter we could identify 8 more reports [8,9,13-24]. Such aneurysms have been thought to occur subsequent to inflammatory processes in the vicinity of the vessel and can rupture into the gallbladder cystic duct or bile duct with resultant haemobilia or rarely rupture into the peritoneal cavity [17,25]. Exceptionally they may be incidentally detected in imaging studies [26].…”
Section: Discussionmentioning
confidence: 99%
“…Some patients having typical obstructive jaundice and hemophilia may additionally need endoscopic retrograde cholangiopancreatography, CBD exploration or transhepatic biliary drainage to vacate the clot in the event the jaundice doesn't get relieved [49,52]. Natural or spontaneous rupture of normal cystic artery is undoubtedly an extremely exceptional reason behind hemoperitoneum [53]. Medical co-morbidity, for instance, arteriosclerosis, diabetes, arterial hypertension and long-term usage of corticosteroid are the most prevalent components liable for vascular fragility [53].…”
Section: Hemobilia Due To Cystic Artery Pseudoaneurysmmentioning
confidence: 99%
“…Natural or spontaneous rupture of normal cystic artery is undoubtedly an extremely exceptional reason behind hemoperitoneum [53]. Medical co-morbidity, for instance, arteriosclerosis, diabetes, arterial hypertension and long-term usage of corticosteroid are the most prevalent components liable for vascular fragility [53]. Selective embolization is an efficient and also a noninvasive treatment alternative, which can result in ischemic gallbladder necrosis few days following the treatment [53].…”
Section: Hemobilia Due To Cystic Artery Pseudoaneurysmmentioning
confidence: 99%